Electrosynthesis and modification of titania nanotubes and incorporation of manganese-nickel oxides for supercapacitor application - Muhammad, Muzakir Muhammad (2021)
Highly ordered titania nanotubes (TNTs) as a 1D nanostructured material have received a lot of interest for supercapacitor applications due to their large surface area and relatively low cost. In this study, TNTs was synthesized by anodization in glycerol-based electrolytes. Electrochemical reduction process was used to modify the TNTs to overcome its high resistivity. The reduced titania nanotubes (R-TNTs) show improved capacitance of 2.28 mF cm-2 which is 7 times higher than TNTs. The R-TNTs exhibit a rectangular cyclic voltammograms and symmetrical triangular charge-discharge curves which are ideal characteristics of electric double layer capacitors (EDLCs). Furthermore, MnO2, NiO and binary NiMn2O4 were incorporated into the nanotubular structures of R-TNTs by pulse electrodeposition (PED) to enhance the capacitive performance of R-TNTs. The capacitance increased to 50.81 mF cm-2, 16.57 mF cm-2 and 97.52 mF cm-2 for MnO2/R-TNTs, NiO/R-TNTs and NiMn2O4/R-TNTs, respectively. All cyclic voltammograms and galvanostatic charge-discharge curves from these samples measured in 1M KCl using three electrode-configuration indicate a pseudocapacitive contribution from the deposited metal oxides. The highest capacitance obtained for the NiMn2O4/R-TNTs composite is attributed to the synergistic effects of the MnO2 and NiO deposited onto high conductivity RTNTs. Physical characterization of all the synthesized samples was conducted by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Higher energy and power density of 5.31 mWh cm-2 and 190.91 mW cm-2 respectively were obtained for NiMn2O4/R-TNTs asymmetric cell in two-electrode configuration.